Can an Algorithm be Agonistic? Ten Scenes from Life in Calculated Publics - Crawford, Kate (Science, Technology & Human Values, 2016)
This paper explores how political theory may help us map algorithmic logics against different visions of the political. Drawing on Chantal Mouffe’s theories of agonistic pluralism, this paper depicts algorithms in public life in ten distinct scenes, in order to ask the question: what kinds of politics do they instantiate? Algorithms are working within highly contested online spaces of public discourse, such as YouTube and Facebook, where incompatible perspectives coexist. Yet algorithms are designed to produce clear “winners” from information contests, often with little visibility or accountability for how those contests are designed. In isolation, many of these algorithms seem the opposite of agonistic: much of the complexity of search, ranking and recommendation algorithms is non-negotiable and kept far from view, inside an algorithmic “black box”. But what if we widen our perspective? This paper suggests agonistic pluralism as both a design ideal for engineers, as well as a provocation to understand algorithms in a broader social context: rather than focusing on the calculations in isolation, we need to account for the spaces of contestation where they operate.